2021
DOI: 10.12688/f1000research.25522.2
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on self-harm and suicidal behaviour: update of living systematic review

Abstract: Background: The COVID-19 pandemic has caused considerable morbidity, mortality and disruption to people’s lives around the world. There are concerns that rates of suicide and suicidal behaviour may rise during and in its aftermath. Our living systematic review synthesises findings from emerging literature on incidence and prevalence of suicidal behaviour as well as suicide prevention efforts in relation to COVID-19, with this iteration synthesising relevant evidence up to 19th October 2020. Method:  Automated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
1
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(115 citation statements)
references
References 140 publications
7
93
1
9
Order By: Relevance
“…There is also a possibility that some patients who would have presented to their GP with self-harm presented to hospital instead. However, the magnitude of the reductions that we observed in April 2020 is in line with those observed internationally [32] . Furthermore, evidence from UK hospitals has shown that there were reductions in self-harm presentations of a similar degree to those that we observed [33] .…”
Section: Discussionsupporting
confidence: 90%
“…There is also a possibility that some patients who would have presented to their GP with self-harm presented to hospital instead. However, the magnitude of the reductions that we observed in April 2020 is in line with those observed internationally [32] . Furthermore, evidence from UK hospitals has shown that there were reductions in self-harm presentations of a similar degree to those that we observed [33] .…”
Section: Discussionsupporting
confidence: 90%
“…Various factors associated with mental health included misinformation, lack of knowledge, socioeconomic problems, social media use, and isolation/quarantine issues. The systematic review showed significantly increased depression, fear, anxiety, stress, suicidal behavior, job loss, financial crisis, nutrition disorders and increase work load in medical personnel ( BC et al., 2021 ; Gao et al, 2020 ; Goodwin et al, 2020 ; John et al., 2020 ; Salari et al, 2020 ). These factors could lead to self-harm or suicidal behavior.…”
Section: Discussionmentioning
confidence: 99%
“… Andriessen, 2006 , John et al, 2020 , Ståhl and MacEachen, 2021 , Statistics Canada 2021e , Calderon-Anyosa and Kaufman, 2021 …”
Section: Uncited Referencesmentioning
confidence: 99%